Distribution of Pre and Post Test Score and the Level of Errors in Answering Questions in the Participants of Education and Nutrition Counseling Training in Non-communicable Diseases - Supriyono Supriyono (Indonesian Journal of Economics, Social, and Humanities, 2020)
This study aims to evaluate the results of pre-test and post-test scores as well as the level of error in participants in education training and nutrition counseling in non-communicable diseases at the Batam health training center in 2016. This study was observational with a cross sectional approach. The population in this study used a saturated sample, where the sample used was the pre-test and post-test scores of all participants who attended the training, which were 30 respondents. To determine the relationship between variables using the Wilcoxon Signed Ranks Test. The results of the analysis using the Wilcoxon Signed Ranks Test between the pre-test and post-test values, obtained a Z value of -4.582 with a p value of .000 <0.05, so there is a significant difference between the pre-test and post-test values. The average pre-test with 30 questions given to participants was 53.56 with a standard deviation of 11.04. While the post-test average of 30 questions given to participants was 67.33 with a standard deviation of 9.45. There was a change of 13.78% of the participant's knowledge score before and after the training. From 30 questions, from pre-test to post-test there was a change in error rate as follows, 70% had an increase, 6.67% remained and 23.33% had a decrease.